Interruption of Onchocerca volvulus Transmission in the Abu Hamed Focus, Sudan - Higazi, Tarig B. (The American Society of Tropical Medicine and Hygiene, 2013)
Abu Hamed, Sudan, the northernmost location of onchocerciasis in the world, began community-directed treatment with ivermectin (CDTI) in 1998, with annual treatments enhanced to semiannual in 2007. We assessed the status of the parasite transmission in 2011 entomologically, parasitologically, and serologically. O-150 pool screening showed no parasite DNA in 17,537 black flies collected in 2011 (95% confidence interval upper limit [95% CI UL] = 0.023). Skin microfilariae, nodules, and signs of skin disease were absent in 536 individuals in seven local communities. Similarly, no evidence of Onchocerca volvulus Ov16 antibodies was found in 6,756 school children ≤ 10 years (95% CI UL = 0.03%). Because this assessment of the focus meets the 2001 World Health Organization (WHO) criteria for interrupted transmission, treatment was halted in 2012, and a post-treatment surveillance period was initiated in anticipation of declaration of disease elimination in this area. We provide the first evidence in East Africa that long-term CDTI alone can interrupt transmission of onchocerciasis.